Analisis Spasial Agihan Lahan Kritis di Kabupaten Sragen Provinsi Jawa Tengah - Rahmatika, Rosita; , Ir. Taryono, M. Si; , Agus Anggoro Sigit, S. Si, M. Sc (2014)
Critical land distribution is needed to reduce the risk of disasters that may arise and improve soil fertility that has been lost. This research aimed to determine critical land distribution in Sragen regency and to find out the result of carefulness step critical land mapping in the research area and to find out the alternative land management. The research method is used in this research is quantitative method tiered weighted by multiplying the scores on each parameters with a predetermined weight value magnitude. The parameters are used to assess the critical land consists of land cover parameters, slope, erosion hazard, agriculture productivity, and management of the area. Each parameters overlaying accordance with the criteria of each region or referrals land functions including protected areas, agricultural cultivated areas, and protected areas outside the forest area. The research findings show that critical land at Sragen regency spread at some subdistrict such as Jenar, Tangen, Gesi, Sukodono, Mondokan, Tanon, Sumberlawang, Miri, Gemolong, Kalijambe, Masaran, Kedawung, Sambirejo, and Gondang subdistrict. The level of accuracy study was 76.67% according to the interpretation of the results and observations in the field. The alternative of land management which suitable is make rehabilitation land and forest by using replanting and reforestation. Planting of seasonal plants or production plants are very helpful in reducing the critical land area. Besides being able to create a cool the surrounding area, forest or plant has functions as a regulator of the water system and prevents or reduces the erosion and landslides.